GAP FILLERS OR PIONEERS: INFORMAL WATER SUPPLIERS IN PERI-URBAN AREAS OF THE TECHIMAN MUNICIPALITY OF GHANA - Kwoyiga, L. (UDS International Journal of Development, 2021)
There is continuous expansion and growth of urban and peri urban areas in Sub-Saharan Africa with projections indicating that this will double. Some peri-urban areas such as those in the Techiman municipality of Ghana are experiencing this trend. Nonetheless, the spate of growth of these areas outstrips the supply of utilities by municipal water distribution networks. As a result, some areas have little or no public provision. In order to address the water supply challenge, places with favourable hydrological settings are witnessing the emergence of informal water suppliers as â€œgap fillersâ€ or â€œpioneersâ€, providing water services. Noteworthy, however, existing studies about informal water suppliers in peri-urban areas in Ghana lump them together, without considering the water source. This study differs in that it specifically examines the evolution and the features of informal water suppliers who privately and independently abstract and supply groundwater. Additionally, it attempts to understand the nature of informality of the suppliers and the possibility of formalisation. The paper is an exploratory study using the case of private mechanised borehole operators who supply water in their respective areas. The findings showed that in some peri-urban areas in the Techiman municipality, some dwellers constructed and operated mechanised boreholes, which provide in-situ water and utilities to others. They are mostly pioneer water suppliers in some of the areas. Their services are informal by nature because they are largely independent of the formal sector and apply informal arrangements in rendering their services. Seen also as business enterprises, they are not licenced. However, the boreholes are registered with the Municipal Assembly, which indicated some level of formalisation. The study recommended that efforts to formalise them further should focus on improving water quality monitoring for consumption and promoting sustainable abstraction.